OC-037 The Increasing Role Of Enhanced Sedation Assisted Ercp: Important Lessons For Service Provision. (9th June 2014) - Joshi, D; Paranandi, B; El Sayed, G; Johnson, G; Chapman, MH; Pereira, SP; Webster, GJ
Abstract : Introduction: ERCP in the UK has historically been performed under conscious sedation (SED). However, given the increasing complexity of cases the role of enhanced sedation assisted ERCP (ENS ERCP) is increasing. A previous audit iat UCLH showed that intolerance of SED was a major factor in ERCP failure. BSG guidance was issued in 2011 regarding the use of propofol sedation for ERCP in the UK .1 We describe our experience of ENS ERCP and highlight the importance of the regular availability of this service. Methods: Our prospective ERCP database was interrogated to include cases between Jan-Nov 2013. Two dedicated ENS ERCP lists run weekly at UCLH. Data collection included procedural information, patient demographics, ASA status, Cotton grade of difficulty (1–4), and endoscopic/anaesthetic complications. ENS ERCP was defined as the use of propofol +/- fentanyl without the need for intubation. ENS was administered by consultant anaesthetists. Data presented as median with range. Comparison was made between SED and ENS ERCP patients. Results: During the 10 month study period 629 ERCPs were performed in 532 patients (52% male). 423 procedures were performed under SED and 139 under ENS. ENS patients were younger compared to SED patients (54, 9–88 years vs. 66, 20–96 years, p < 0.0001) but ASA grade 1–2 status was similar between the two groups (84 vs. 78%, p=NS). An increased number of Cotton grade 3–4 ERCPs were perfomed in the ENS group (64 vs. 34%, p < 0.0001). Common indications for ENS included previously uncomfortable/failed procedure (30%), biliary/pancreatic sphincter of Oddi manometry (24%) and single operator cholangioscopy (20%). Patient choice accounted for only 4% of cases. 59% of cases were tertiary referrals, 12% of which had failed previously. 77% of referrals were elective cases, 12% urgent day-case referrals and 11% urgent in-patients. ERCP was completed successfully in 95% of cases. Anaesthetic complications occurred in 3 cases all relating to over sedation requiring intubation. ERCP-related complications occurred in 5% of cases. Where previous SED ERCP was unsuccessful due to patient intolerance, the procedure was completed in all cases using ENS. Conclusion: To date ENS ERCP has predominately been used for previously failed/poorly tolerated procedures and Cotton Grade 3–4 ERCPs. ENS ERCP improves outcomes and is safe when delivered with anaesthetic support. It is likely to be increasingly requested by patients and referrers. Regular ENS provision should be offered by all endoscopy units offering ERCP, and the anaesthetic resource and funding implications will need to be pursued. Reference: 1 Guidance for the use of propofol sedation for adult patients undergoing ERCP and other complex upper GI endoscopy procedures, April 2011. RCoA and BSG guidance Disclosure of Interest: None Declared.